0161 Strategies for Enhancing Recruitment of Adults for Randomized Controlled Trial Among Heterogenous Sample of Cancer Survivors with Insomnia Amid the Covid Pandemic. (25th May 2022) - Loomis, Dianne; Tyrpak, Donna; Larkin, Karen; Kwon, Misol; Foltz-Ramos, Kelly; Mclaughlin, Pamela; Gaughan, Mary Rose; Dickerson, Suzanne; Dean, Grace
Abstract: Introduction: Challenges associated with recruiting participants in a longitudinal research study have been recognized yet remain a major barrier for researchers. The current study details strategies used in recruiting a heterogenous sample of cancer survivors with insomnia from multiple clinical sites, referral sources and outreach. Methods: Enrollment goals were 158 participants over 3 years (June 2019 to May 2022). Recruitment strategies included 1) face-to-face (FTF) recruitment at hospital clinics; 2) posting recruitment flyers in clinical settings; 3) completion of insomnia screening instrument at community clinic sites; 4) research registries; 5) institutional social media outreach; 6) community events; 7) PI interview and request for study volunteers in local newspaper; and 8) ongoing engagement and communication with recruited participants. Results: 108 of 158 participants have been recruited and completed baseline surveys; 9 participants dropped out. To date, 42 of 49 (85.7%) participants have completed the 12-month study. June 2019 through December 2019 FTF recruitment occurred, where 104 were eligible and 32 (30.76%) were enrolled. Due to changes in study personnel and the COVID pandemic restricting access to in-person recruitment and enrollment, the study pivoted to develop protocols for electronic consent and enrollment using video conferencing. In addition, research databases, institutional social media, community events and local newspaper were utilized, where 76 of 239 (31.79%) interested participants enrolled. The most effective recruitment strategies included on-site FTF recruitment (57.9%) and local newspaper interview (13.88%). The local newspaper interview was the most cost-effective considering personnel costs associated with FTF recruitment. Conclusion: Despite the onset of the COVID pandemic during the recruitment phase, we were able to pivot and employ innovative techniques to meet our targeted enrollment goal for the projected study deadline. FTF recruitment, perceived value by clinic staff in benefitting cancer survivors, and participants' acceptance of video-conferencing were significant contributors. The importance of building and maintaining relationships with providers and nurses in local clinical sites cannot be underestimated. Support (If Any): This research was funded by R01 NR018215 (Dean) by the National Institute of Nursing Research.